2016
DOI: 10.3390/ijerph13100976
|View full text |Cite
|
Sign up to set email alerts
|

Non-Obese Diabetes and Its Associated Factors in an Underdeveloped Area of South China, Guangxi

Abstract: Background: Little research has been conducted on the prevalence of diabetes mellitus in underdeveloped areas in China, especially stratified into obesity and non-obese diabetes. The aim of the present study was to investigate the prevalence and associated factors of non-obese diabetes in an underdeveloped area in South China, Guangxi. Methods: Data derived from the Chinese Health and Nutrition Survey 2010–2012 involved a sample of 3874 adults from Guangxi. Questionnaires and oral glucose-tolerance tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Of note, our subjects had a lower BMI, while waist circumference was relatively high. According to Tang et al [36], even persons with normal BMI but with central abdominal obesity might place them at risk for non-obese diabetes. In fact, abdominal obesity has been proven to be the best predictor of type 2 diabetes, compared to BMI, waist/hip ratio, and other anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our subjects had a lower BMI, while waist circumference was relatively high. According to Tang et al [36], even persons with normal BMI but with central abdominal obesity might place them at risk for non-obese diabetes. In fact, abdominal obesity has been proven to be the best predictor of type 2 diabetes, compared to BMI, waist/hip ratio, and other anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“… 45 And another study reported that 68.2% of instances of newly detected T2D was those of non-obese T2D in southern China. 46 Compared with obese individuals, the key defect that causes the development of hyperglycemia in T2D in non-obese individuals is impaired pancreatic insulin secretion and decreased insulin resistance. 45 , 47 It is worth noting that the increased risk of cardiovascular disease in non-obese type 2 diabetic patients is similar to that of obese type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 For example, in some Asian countries, the proportion of non-obese diabetes accounted for over 60% of all diabetes cases. [4][5][6] Emerging evidence suggests that non-obese diabetes is associated with a higher risk of cardiovascular diseases than obese diabetes. [7][8][9] Moreover, several large-scale prospective cohort studies have found that non-obese diabetes is associated with an approximately two-fold higher risk of mortality than obese diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a well‐established risk factor for type 2 diabetes (hereafter, diabetes) 1,2 ; however, a proportion of individuals develop diabetes in its absence 3 . For example, in some Asian countries, the proportion of non‐obese diabetes accounted for over 60% of all diabetes cases 4–6 . Emerging evidence suggests that non‐obese diabetes is associated with a higher risk of cardiovascular diseases than obese diabetes 7–9 .…”
Section: Introductionmentioning
confidence: 99%